Afterword: Why Ethnography? - Garriott, William Campbell (Social justice, 2017)
The article discusses the use of an ethnographic approach to criminal justice administration, through largely focusing on the U.S. An overview of the relationship between U.S. criminal law and U.S. immigration policy, including in regard to the deportation of criminals under U.S. President Barack Obama and U.S. President Donald Trump's focus on immigration enforcement, is provided.